Ionic polymer as well as preparation method and application thereof

By mixing the carboxyl-containing polymer with metal ionic solution in the preparation of ionic polymers, the solvent is removed to make it react uniformly, which solves the problems of high equipment requirements and poor optical performance, and achieves no white spots, low yellowness, and low Haze and high light transmittance polymer.

CN119161519APending Publication Date: 2024-12-20JIANGSU SAILBOAT PETROCHEMICAL CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411424489.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing ionic polymer preparation methods have problems such as high equipment requirements, yellowness, haze, light transmittance and poor white spot phenomena.

Method used

By mixing the carboxyl-containing polymer with the metal ion-containing solution and removing the solvent, the metal compound is uniformly adhered to the polymer surface, and reacted to reduce white spots caused by unreacted and reduce equipment requirements.

Benefits of technology

Ion polymers with no white spots, low yellowness, low haze and high light transmittance are achieved, reducing equipment requirements and improving optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081774300000171
    Figure BDA0005081774300000171
Patent Text Reader

Abstract

The invention relates to an ionic polymer and a preparation method and application thereof, and the preparation method comprises the following steps: mixing a carboxyl-containing polymer with a metal ion-containing solution to obtain a first mixture; removing the solvent in the first mixture to obtain a second mixture; based on 100% of the mass of the solvent, the mass of the removed solvent is 50-100%; and reacting the second mixture to obtain the ionic polymer. According to the preparation method provided by the invention, after the carboxyl-containing polymer and the metal ion-containing solution are mixed, the solvent in the obtained mixture is removed, so that the metal compound is uniformly attached to the surface of the carboxyl-containing polymer in a solid form, and the problem that the carboxyl-containing polymer and the metal compound are difficult to uniformly mix is solved; and the preparation method of the ionic polymer does not need equipment such as a liquid metering pump, so that the requirement on the equipment for preparing the ionic polymer is reduced on the whole, and the quality of the ionic polymer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of ionic polymers, and in particular relates to an ionic polymer and a preparation method and application thereof. Background Art

[0002] Ionic polymers are widely used in consumer products such as food, medical vacuum skin packaging, high-end cosmetic packaging, golf and other sports equipment due to their high gloss, transparency, excellent mechanical properties and hot-tack properties. In addition, due to their non-polar covalent skeleton and polar ion cluster structure, such ionic polymers can also be used in self-repairing, blending modification, ionic interlayers and other fields. For most of the above applications, the desired ionic polymer needs to have low haze and no impurities such as white spots.

[0003] The preparation method of ionic polymer is well known in the art, and the preparation method comprises: neutralizing a carboxyl-containing polymer so that at least a portion of the carboxyl groups in the corresponding polymer are neutralized by one or more metal ions to obtain an ionic polymer (hereinafter also referred to as a melting method). At present, the method mainly has the following aspects that need to be improved: first, the existing method is that a solution of metal ions is mixed with a carboxyl-containing polymer in an extruder, and the addition of the solution of metal ions requires accessories such as a liquid metering pump, and since the carboxyl-containing polymer is insoluble in the solvent (usually water) in the solution of metal ions, in order to enable the two to be mixed as fully as possible, equipment such as a twin / single screw extruder with sufficient transport and mixing capacity is required, and since the addition of the solution brings in more solvent, it is necessary to remove the solvent with a higher vacuum degree in the devolatilization component zone, so the requirements for the equipment are relatively high; in addition, there will be metal compounds remaining due to unreacted, and the yellowness, haze, light transmittance and other properties of the ionic polymer obtained by the method and the phenomena such as white spots need to be further improved.

[0004] US3264272 discloses a method for obtaining an ionic polymer by melt-blending an α-olefin / α,β-unsaturated carboxylic acid copolymer in a molten state with an aqueous solution or powder of a metal compound. The transparency of the ionic polymer obtained by this method cannot reach the desired level.

[0005] US4882393 discloses a continuous method for preparing an ionic polymer by copolymerization of ethylene and an unsaturated carboxylic acid metal salt, but the preparation process of the unsaturated carboxylic acid metal salt used in this method is very expensive; in addition, the amount of solvent required for metering the unsaturated carboxylic acid salt is very high, and the solvent must be removed from the product through a relatively complicated process; and in this process, when a masterbatch containing zinc oxide is used to neutralize the ethylene copolymer, ionic crosslinking does not occur, and white spots are easily generated in the product. When a zinc acetate aqueous solution is used for neutralization, ionic crosslinking can occur, but the zinc acetate solution corrodes the extruder, so the product obtained by this method appears brown or black.

[0006] EP0193110 discloses a method for preparing an ionic polymer with improved uniformity, but in this method, the extruder must be corrosion-resistant and must be equipped with more than two outlets for devolatilization to prevent the generated gas from being squeezed out of the degassing port and then being sucked back in to produce spots. In addition, the above method requires a relatively long screw reaction zone length for effective devolatilization.

[0007] Therefore, there is an urgent need to develop a method for preparing an ionic polymer that has low equipment requirements and can improve the yellowness, haze and light transmittance of the ionic polymer while reducing the generation of white spots. Summary of the invention

[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an ionic polymer and a preparation method and application thereof. By designing raw materials and preparation processes, the requirements of the ionic polymer on production equipment are reduced, and the yellowness, haze and light transmittance of the ionic polymer can be improved, thereby reducing the occurrence of white spots.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing an ionic polymer, the preparation method comprising:

[0011] A carboxyl-containing polymer is mixed with a solution containing metal ions to obtain a first mixture; the solvent in the first mixture is removed to obtain a second mixture; based on the mass of the solvent being 100%, the mass of the removed solvent is 50-100%; the second mixture is reacted to obtain the ionic polymer.

[0012] The preparation method of the ionic polymer provided by the present invention is to use a carboxyl-containing polymer as a raw material and react it with a solution containing metal ions to prepare the ionic polymer. The reaction enables at least a part of the carboxyl groups in the carboxyl-containing polymer to be neutralized by one or more metal ions. In the preparation method provided by the present invention, the carboxyl-containing polymer and the metal ion-containing solution are uniformly mixed and then the solvent is removed, so that the metal compound is uniformly attached to the surface of the carboxyl-containing polymer in a solid form, and the carboxyl-containing polymer and the metal compound are uniformly mixed, so that the two can fully react, and white spots caused by incomplete reaction are reduced; compared with the method of injecting the metal ion solution into the liquid pump into the extruder to react in the prior art, the preparation method of the ionic polymer provided by the present invention does not require equipment such as a liquid metering pump, and at the same time, since the carboxyl-containing polymer and the metal compound are mixed more uniformly, the mixing capacity requirements of the production equipment are lower; since the carboxyl-containing polymer and the metal compound are mixed more uniformly and the solvent is removed, the vacuum required in the devolatilization zone can be reduced to a certain extent, the requirements for the production equipment for preparing the ionic polymer are generally reduced, and the quality of the ionic polymer is improved, so that the obtained ionic polymer has no white spots, and the yellowness, haze, light transmittance, etc. are improved, so as to obtain an ionic polymer with improved optical properties.

[0013] Taking the mass of the solvent as 100%, the mass of the solvent removed is 50-100%, for example, it can be 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, etc.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] As a preferred technical solution, the concentration of carboxyl in the carboxyl-containing polymer is 0.2-25 mol% (for example 0.5 mol%, 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, etc.), and further preferably is 1-12 mol% (for example 1.2 mol%, 1.5 mol%, 2.5 mol%, 3.5 mol%, 4.5 mol%, 5.5 mol%, 6.5 mol%, 7.5 mol%, 8.5 mol%, 9.5 mol%, 10.5 mol%, 11.5 mol%, 11.8 mol%, etc.).

[0016] The melt index of the carboxyl-containing polymer of the present invention is measured according to ASTM D1238 (2.16 kg, 190° C.) standard, and the melt index of the carboxyl-containing polymer under 2.16 kg, 190° C. conditions is 1-1000 g / 10 min (for example, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min, 60 g / 10 min, 70 g / 10 min, 80 g / 10 min, 90 g / 10 min, 95 g / 10 min, 100 g / 10 min, 200 g / 10 min, 300 g / 10 min, 400 g / 10 min, 500 g / 10 min, 600 g / 10 min, The preferred embodiment of the present invention is 20-600g / 10min (for example, 25g / 10min, 35g / 10min, 45g / 10min, 55g / 10min, 65g / 10min, 75g / 10min, 85g / 10min, 95g / 10min, 105g / 10min, 150g / 10min, 250g / 10min, 350g / 10min, 450g / 10min, 550g / 10min, 580g / 10min, etc.).

[0017] Preferably, the carboxyl group-containing polymer comprises a copolymer of an α-olefin and an unsaturated carboxylic acid monomer and / or an unsaturated carboxylic acid derivative monomer.

[0018] Preferably, the α-olefin has 2-8 carbon atoms (eg, 2, 3, 4, 5, 6, 7, etc.), more preferably 2-3.

[0019] Preferably, the unsaturated carboxylic acid monomer includes any one of acrylic acid, methacrylic acid, ethacrylic acid, itaconic acid, maleic acid or fumaric acid, or a combination of at least two thereof.

[0020] Preferably, the unsaturated carboxylic acid derivative monomer includes any one of methyl hydrogen maleate, ethyl hydrogen maleate, propyl hydrogen maleate, hexyl hydrogen maleate, ethyl hydrogen fumarate or maleic anhydride, or a combination of at least two thereof.

[0021] Preferably, the carboxyl group-containing polymer includes any one of ethylene-methacrylic acid copolymer, ethylene-acrylic acid copolymer or ethylene-ethylacrylic acid copolymer, or a combination of at least two thereof.

[0022] Preferably, the metal ions include metal ions formed from at least one metal of Group IA, Group IIA, Group IIIA or transition metals of the periodic table.

[0023] Preferably, the chemical valence of the metal ion includes any one of monovalent, divalent or trivalent, or a combination of at least two of them.

[0024] Preferably, the metal ions include any one or a combination of at least two of lithium ions, sodium ions, potassium ions, rubidium ions, cesium ions, beryllium ions, magnesium ions, calcium ions, strontium ions, barium ions or zinc ions, more preferably any one or a combination of at least two of potassium ions, sodium ions, lithium ions, magnesium ions, calcium ions or zinc ions, more preferably any one or a combination of at least two of potassium ions, sodium ions, lithium ions or zinc ions.

[0025] Preferably, the metal ions are derived from metal compounds, and the metal compounds include any one of metal hydroxides, metal inorganic salts or metal organic salts, or a combination of at least two of them.

[0026] Preferably, the metal hydroxide includes any one of lithium hydroxide, sodium hydroxide or potassium hydroxide, or a combination of at least two of them.

[0027] Preferably, the metal inorganic salt comprises zinc sulfate and / or zinc chloride.

[0028] Preferably, the metal organic salt includes any one of sodium acetate, calcium acetate, magnesium acetate, zinc acetate or zinc formate, or a combination of at least two thereof.

[0029] Preferably, the metal compound includes any one of lithium hydroxide, sodium hydroxide, potassium hydroxide or zinc acetate, or a combination of at least two thereof.

[0030] Preferably, the solution containing metal ions is obtained by mixing the metal compound with the solvent.

[0031] Preferably, the solvent includes any one of water, methanol or ethanol or a combination of at least two thereof, more preferably water.

[0032] Preferably, based on the mass of the solution containing metal ions as 100%, the mass of the metal compound is 30-50%, for example, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, etc.

[0033] Preferably, the molar ratio of the metal ion to the carboxyl group in the carboxyl-containing polymer is (0.2-0.7):1, for example, it can be 0.22:1, 0.24:1, 0.26:1, 0.28:1, 0.3:1, 0.32:1, 0.34:1, 0.36:1, 0.38:1, 0.4:1, 0.42:1, 0.44:1, 0.46:1, 0.48:1, 0.5:1, 0.52:1, 0.55:1, 0.58:1, 0.6:1, 0.62:1, 0.65:1, 0.68:1, etc.

[0034] Preferably, the carboxyl group-containing polymer is ground into powder before the mixing.

[0035] Preferably, the first mixture is dried to remove the solvent.

[0036] Preferably, the drying temperature is 20-90°C (for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, etc.), and further preferably is 30-70°C (for example, 31°C, 33°C, 38°C, 42°C, 46°C, 48°C, 52°C, 54°C, 58°C, 62°C, 64°C, 66°C, 68°C, etc.).

[0037] The drying temperature cannot be too high, otherwise the carboxyl-containing polymer will turn yellow or even melt; the drying temperature cannot be too low, otherwise the solvent cannot be removed.

[0038] Preferably, the drying time is 24-120h (for example, 25h, 30h, 40h, 50h, 60h, 70h, 80h, 90h, 100h, 110h, etc.), and more preferably 48-72h (for example, 51h, 52h, 54h, 56h, 58h, 62h, 64h, 66h, 68h, 71h, etc.).

[0039] The drying time cannot be too long, otherwise the carboxyl-containing polymer will turn yellow, nor can it be too short, otherwise the solvent cannot be removed.

[0040] Preferably, the drying is performed under vacuum conditions.

[0041] Preferably, based on the mass of the solvent being 100%, the mass of the solvent removed is 70-100%, for example, it may be 71%, 74%, 76%, 79%, 81%, 84%, 86%, 89%, 91%, 94%, 96%, 99%, etc.

[0042] Preferably, the reaction temperature is 120-300°C, for example, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, etc.

[0043] Preferably, the reaction time is 5-15 s, for example, it can be 5 s, 6 s, 7 s, 8 s, 9 s, 10 s, 11 s, 12 s, 13 s, 14 s, etc.

[0044] Preferably, the reaction further comprises a melting step before proceeding.

[0045] Preferably, the melting temperature is 120-300°C, for example, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, etc.

[0046] Preferably, the melting time is 5-15 s, for example, it can be 5 s, 6 s, 7 s, 8 s, 9 s, 10 s, 11 s, 12 s, 13 s, 14 s, etc.

[0047] Preferably, after the reaction is completed, the step of devolatilizing components is further included.

[0048] Preferably, the devolatilization is carried out under a vacuum degree of -10 to -950 mbar, for example, -50 mbar, -100 mbar, -150 mbar, -200 mbar, -250 mbar, -300 mbar, -350 mbar, -400 mbar, -450 mbar, -500 mbar, -550 mbar, -600 mbar, -650 mbar, -700 mbar, -750 mbar, -800 mbar, -850 mbar, -900 mbar, etc.

[0049] Further preferably, the devolatilization is carried out under a vacuum degree of -50 to -600 mbar, for example, -55 mbar, -60 mbar, -70 mbar, -80 mbar, -90 mbar, -120 mbar, -180 mbar, -220 mbar, -280 mbar, -320 mbar, -380 mbar, -420 mbar, -480 mbar, -520 mbar, -580 mbar, etc.

[0050] Preferably, the devolatilization time is 30-60 s, for example, 32 s, 34 s, 36 s, 38 s, 40 s, 42 s, 44 s, 46 s, 48 ​​s, 50 s, 52 s, 54 s, 56 s, 58 s, etc.

[0051] In the present invention, the devolatilization of components can be carried out in one stage or in at least two stages; when carried out in one stage, the vacuum degree can be set to -500 to -950 mbar (preferably -500 to -700 mbar), and the time can be 30-60 s; when carried out in at least two stages, the devolatilization processes are named as the first devolatilization component and the second devolatilization component, etc. in order, the vacuum degree of the first devolatilization component can be set to -500 to -950 mbar (preferably -500 to -700 mbar), and the time can be 15-30 s, and the remaining devolatilization processes can be independently carried out under the conditions of a vacuum degree of -10 to -200 mbar (preferably -50 to -180 mbar) and a time of 15-30 s.

[0052] In the preparation method provided by the present invention, water produced by the reaction and the solvent contained in the second mixture are removed by devolatilization. Since the solvent is removed after the carboxyl-containing polymer is mixed with the metal ion-containing solution, the vacuum degree required for devolatilization can be reduced to a certain extent.

[0053] Preferably, the melting, reaction and devolatilization are carried out in a continuous extrusion system.

[0054] The preparation method of the ionic polymer provided by the present invention can be carried out by a reactive extrusion process, and any continuous extrusion system can be used. The continuous extrusion system must have basic transport and mixing capabilities, and the continuous extrusion system has: a feed zone for allowing the addition of solid materials, a melting zone for fully mixing materials, a reaction zone, and a devolatilization zone; the reaction zone is located after the melting zone, and the material can pass through one or more of the devolatilization zones to remove the solvent. When there are multiple (at least 2) devolatilization zones, the vacuum degree of the first devolatilization zone can be set to -500 to -950 mbar (preferably -500 to -700 mbar), and the time can be 15-30 seconds, and the vacuum degree of the remaining devolatilization zones can be independently set to -10 to -200 mbar (preferably -50 to -180 mbar), and the time can be 15-30 seconds; the devolatilization zone is located after the reaction zone; after the material enters the continuous extrusion system, it passes through the melting zone, the reaction zone, and the devolatilization zone in sequence to complete the preparation of the ionic polymer.

[0055] Preferably, the continuous extrusion system comprises a twin-screw extruder and / or a single-screw extruder.

[0056] Preferably, the twin-screw extruder comprises a co-rotating intermeshing twin-screw extruder or a counter-rotating intermeshing twin-screw extruder.

[0057] Preferably, the screw aspect ratio of the continuous extrusion system is (30-56):1, for example, it can be 32:1, 34:1, 36:1, 38:1, 40:1, 42:1, 44:1, 46:1, 48:1, 50:1, 52:1, 54:1, etc.

[0058] Preferably, after the devolatilization is completed, the process further comprises the steps of sequentially cooling and granulating the reaction product.

[0059] Preferably, the preparation method specifically comprises the following steps:

[0060] (1) mixing a metal compound with water to obtain a solution containing metal ions; mixing a carboxyl-containing polymer with the metal ion-containing solution to obtain a first mixture; the concentration of carboxyl groups in the carboxyl-containing polymer is 0.2-25 mol%; the melt index of the carboxyl-containing polymer under the conditions of 2.16 kg and 190° C. is 1-1000 g / 10 min; based on the mass of the metal ion-containing solution as 100%, the mass of the metal compound is 30-50%; the molar ratio of the metal ions to the carboxyl groups in the carboxyl-containing polymer is (0.2-0.7):1;

[0061] (2) drying the first mixture under vacuum conditions at 20-90° C. for 24-120 h to remove 50-100 wt % of water in the first mixture to obtain a second mixture;

[0062] (3) adding the second mixture to a continuous extrusion system, the continuous extrusion system comprising a melting zone, a reaction zone and a devolatilization zone; the second mixture is melted in the melting zone at a temperature of 120-300°C for a time of 5-15 seconds; the melted material reacts in the reaction zone at a temperature of 120-300°C for a time of 5-15 seconds; the reaction product is devolatilized in the devolatilization zone at a vacuum degree of -10 to -950 mbar for 30-60 seconds; the devolatilization reaction product is extruded, cooled and granulated in sequence to obtain the ionic polymer.

[0063] In a second aspect, the present invention provides an ionic polymer, wherein the ionic polymer is prepared by the preparation method described in the first aspect.

[0064] In a third aspect, the present invention provides a use of the ionic polymer as described in the second aspect in sports equipment, cosmetic containers, perfume containers, food packaging, glass composite layers, automotive parts, medical vacuum skin packaging or polar exploration equipment.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] (1) The preparation method provided by the present invention mixes the carboxyl-containing polymer with the solution containing metal ions, and then removes the solvent in the resulting mixture, so that the metal compound is uniformly attached to the surface of the carboxyl-containing polymer in a solid form, thereby solving the problem that the two are difficult to mix uniformly;

[0067] (2) The preparation method provided by the present invention does not require liquid filling equipment such as a liquid metering pump to inject the metal ion-containing solution into the production equipment, and because the carboxyl-containing polymer and the metal compound have been well mixed, the mixing capacity requirements of the subsequent production equipment are relatively low, which generally reduces the equipment requirements for preparing the ionic polymer;

[0068] (3) The preparation method provided by the present invention can improve the quality of the ionic polymer. The obtained ionic polymer has no white spots, lower yellowness and haze, and higher light transmittance, thereby obtaining an ionic polymer with improved optical properties. The ionic polymer obtained by the preparation method provided by the present invention has a yellowness index of 1.0-2.8, a haze of 7.1-13.6%, a near-ultraviolet transmittance of 80.9-86.7%, and a visible light transmittance of 90.8-91.8%. DETAILED DESCRIPTION

[0069] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0070] The sources of some components in the embodiments and comparative examples are as follows:

[0071] (1) Ethylene-methacrylic acid copolymer:

[0072] a. 2.16 kg, 190°C, melt index 60 g / 10 min, methacrylic acid unit mass percentage 15%, purchased from Dow Chemical NUCREL TM 960;

[0073] b. 2.16 kg, at 190°C, with a melt index of 25 g / 10 min and a mass percentage of methacrylic acid units of 15%, purchased from Dow Chemical NUCREL TM 925;

[0074] c.2.16 kg, at 190°C, the melt index is 95 g / 10 min, the mass percentage of methacrylic acid unit is 11%, purchased from Dow Chemical NUCREL TM 699;

[0075] d.2.16 kg, at 190°C, with a melt index of 450 g / 10 min and a mass percentage of methacrylic acid units of 10%, purchased from Dow Chemical NUCREL TM 599;

[0076] (2) Ethylene-acrylic acid copolymer: 2.16 kg, at 190° C., melt index 20 g / 10 min, acrylic acid unit mass percentage 9.7%, purchased from SK Chemical PRIMACOR TM 3460.

[0077] The twin-screw extruder (manufacturer: STEER, model: OMEGA25) used in the following examples and comparative examples has a screw length-to-diameter ratio of 56:1, including a melting zone, a reaction zone and two devolatilization zones. After entering the twin-screw extruder, the material passes through the melting zone, the reaction zone, the first devolatilization zone and the second devolatilization zone in sequence.

[0078] Example 1

[0079] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0080] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM 960 is mixed evenly with sodium hydroxide aqueous solution. Sodium hydroxide and NUCREL TM The molar ratio of methacrylic acid (MAA) units in 960 is 0.3:1;

[0081] (2) placing the mixture obtained in step (1) in a vacuum oven at 50° C. for 48 hours to remove 90 wt % of water in the mixture;

[0082] (3) The mixture from which 90 wt% of water has been removed in step (2) is fed into a twin-screw extruder at a rate of 10 kg / h, melted at 180° C. for 5 seconds in a melting zone, and reacted at 190° C. for 10 seconds in a reaction zone; the reaction product is devolatilized at a vacuum degree of -600 mbar for 15 seconds in a first devolatilization zone, and then devolatilized at a vacuum degree of -50 mbar for 15 seconds in a second devolatilization zone; the reaction product from which water has been removed is extruded, cooled, and granulated in sequence to obtain the ionic polymer.

[0083] Example 2

[0084] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0085] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM After 960 is ground into uniform powder, it is mixed evenly with sodium hydroxide aqueous solution. Sodium hydroxide and NUCREL TM The molar ratio of MAA units in 960 is 0.3:1;

[0086] The remaining steps and process parameters are the same as those in Example 1.

[0087] Example 3

[0088] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0089] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM 960 is mixed evenly with sodium hydroxide aqueous solution. Sodium hydroxide and NUCREL TM The molar ratio of MAA units in 960 is 0.4:1;

[0090] The remaining steps and process parameters are the same as those in Example 1.

[0091] Example 4

[0092] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0093] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM 960 is mixed evenly with sodium hydroxide aqueous solution. Sodium hydroxide and NUCREL TM The molar ratio of MAA units in 960 is 0.5:1;

[0094] The remaining steps and process parameters are the same as those in Example 1.

[0095] Example 5

[0096] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0097] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM 925 is mixed evenly with sodium hydroxide aqueous solution, sodium hydroxide and NUCREL TM The molar ratio of MAA units in 925 is 0.3:1;

[0098] The remaining steps and process parameters are the same as those in Example 1.

[0099] Example 6

[0100] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0101] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM 699 is mixed evenly with sodium hydroxide aqueous solution. Sodium hydroxide and NUCREL TM The molar ratio of MAA units in 699 is 0.3:1;

[0102] The remaining steps and process parameters are the same as those in Example 1.

[0103] Example 7

[0104] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0105] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM599 is mixed evenly with sodium hydroxide aqueous solution. Sodium hydroxide and NUCREL TM The molar ratio of MAA units in 599 is 0.3:1;

[0106] (2) placing the mixture obtained in step (1) in a vacuum oven at 50° C. for 72 hours to remove 95 wt % of water in the mixture;

[0107] The remaining steps and process parameters are the same as those in Example 1.

[0108] Example 8

[0109] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0110] (1) 320 g of zinc acetate was prepared into a 30 wt% aqueous solution of zinc acetate, and NUCREL TM 960 is mixed evenly with zinc acetate aqueous solution. Zinc acetate and NUCREL TM The molar ratio of MAA units in 960 is 0.3:1;

[0111] (2) placing the mixture obtained in step (1) in a vacuum oven at 50° C. for 120 hours to remove 90 wt % of water in the mixture;

[0112] (3) The mixture from which 90 wt% of water has been removed in step (2) is fed into a twin-screw extruder at a rate of 10 kg / h, melted at 180° C. for 5 seconds in a melting zone, and reacted at 190° C. for 10 seconds in a reaction zone; the reaction product is devolatilized at a vacuum degree of -600 mbar for 20 seconds in a first devolatilization zone, and then devolatilized at a vacuum degree of -20 mbar for 15 seconds in a second devolatilization zone; the reaction product from which water has been removed is extruded, cooled, and granulated in sequence to obtain the ionic polymer.

[0113] Example 9

[0114] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0115] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM 3460 is mixed evenly with sodium hydroxide aqueous solution, sodium hydroxide and PRIMACOR TM The molar ratio of acrylic acid units in 3460 is 0.3:1;

[0116] (2) placing the mixture obtained in step (1) in a vacuum oven at 50° C. for 48 hours to remove 90 wt % of water in the mixture;

[0117] (3) The mixture from which 90 wt% of water has been removed in step (2) is fed into a twin-screw extruder at a rate of 10 kg / h, melted at 180° C. for 5 seconds in a melting zone, and reacted at 190° C. for 10 seconds in a reaction zone; the reaction product is devolatilized at a vacuum degree of -700 mbar for 15 seconds in a first devolatilization zone, and then devolatilized at a vacuum degree of -10 mbar for 15 seconds in a second devolatilization zone; the reaction product from which water has been removed is extruded, cooled, and granulated in sequence to obtain the ionic polymer.

[0118] Comparative Example 1

[0119] An ionic polymer and a preparation method thereof, which differs from Example 1 only in that the mixture obtained in step (1) is not dried, that is, step (2) is not performed and the mixture obtained in step (1) is directly fed into a twin-screw extruder, and the remaining process parameters and steps are the same as those in Example 1.

[0120] Comparative Example 2

[0121] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0122] (1) preparing a sodium hydroxide aqueous solution with a concentration of 50 wt % by 40 g of sodium hydroxide;

[0123] (2) Ethylene-methacrylic acid copolymer NUCREL TM 960 was fed into the twin-screw extruder at a rate of 10 kg / h, and at the same time, the sodium hydroxide aqueous solution was fed into the mixing zone of the twin-screw extruder through a liquid metering pump at a rate of 0.9 kg / h. TM The molar ratio of the MAA units in 960 is 0.3:1; the melting, reaction and devolatilization conditions are the same as those in Example 1, and the reaction product after dehydration is extruded, cooled and granulated in sequence to obtain the ionic polymer.

[0124] Comparative Example 3

[0125] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0126] (1) Mix 40 g of sodium hydroxide powder and ethylene-methacrylic acid copolymer NUCREL TM 960 Mix evenly, sodium hydroxide and NUCREL TM The molar ratio of MAA units in 960 is 0.3:1;

[0127] (2) The mixture obtained in step (1) is fed into a twin-screw extruder at a rate of 10 kg / h. The conditions for melting, reaction and devolatilization are the same as those in Example 1. The reaction product after water removal is extruded, cooled and granulated in sequence to obtain the ionic polymer.

[0128] Comparative Example 4

[0129] An ionic polymer and a preparation method thereof, the preparation method comprising:

[0130] Ethylene-methacrylic acid copolymer NUCREL TM 960 was fed into the twin-screw extruder at a rate of 10 kg / h, and 40 g of sodium hydroxide powder was fed into the mixing zone of the twin-screw extruder at a rate of 0.2 kg / h. TM The molar ratio of the MAA units in 960 is 0.3:1. The melting, reaction and devolatilization conditions are the same as those in Example 1. The reaction product after removing water is extruded, cooled and granulated in sequence to obtain the ionic polymer.

[0131] Comparative Example 5

[0132] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0133] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM 960 is mixed evenly with sodium hydroxide aqueous solution. Sodium hydroxide and NUCREL TM The molar ratio of MAA units in 960 is 0.3:1;

[0134] (2) placing the mixture obtained in step (1) in a vacuum oven at 50° C. for 12 h to remove 30 wt % of water from the mixture;

[0135] (3) The mixture from which 30 wt% of water is removed in step (2) is fed into a twin-screw extruder at a rate of 10 kg / h, melted at 180° C. for 5 seconds in a melting zone, and reacted at 190° C. for 10 seconds in a reaction zone; the reaction product is devolatilized at a vacuum degree of -600 mbar for 15 seconds in a first devolatilization zone, and then devolatilized at a vacuum degree of -50 mbar for 15 seconds in a second devolatilization zone; the reaction product from which water is removed is extruded, cooled, and granulated in sequence to obtain the ionic polymer.

[0136] Comparative Example 6

[0137] An ionic polymer and a preparation method thereof, the preparation method comprising the following steps:

[0138] (1) 40 g of sodium hydroxide was prepared into a sodium hydroxide aqueous solution with a concentration of 50 wt %. TM 960 is mixed evenly with sodium hydroxide aqueous solution. Sodium hydroxide and NUCREL TM The molar ratio of MAA units in 960 is 1:1;

[0139] The remaining steps and process parameters are the same as those in Example 1.

[0140] Performance Testing

[0141] (1) White spots: Observe with the naked eye to see if there are white spots;

[0142] (2) Yellowness index: measured by spectrophotometer (HunterLab, UltrascanVIS) according to ASTM E313;

[0143] (3) Haze: measured by spectrophotometer (HunterLab, UltrascanVIS) according to ASTM D1003;

[0144] (4) Transmittance: measured by ultraviolet spectrophotometer (Shimadzu, UV-3600i Plus) according to ASTM D1003. The transmittance in the near-ultraviolet region refers to the average transmittance in the range of 290-380 nm; the transmittance in the visible region refers to the average transmittance in the range of 380-1100 nm.

[0145] The ionic polymers provided in Examples 1-9 and Comparative Examples 1-6 were tested according to the above method. The test results are shown in Table 1:

[0146] Table 1

[0147]

[0148] It can be seen from the test results in Table 1 that no white spots are observed with the naked eye for the ionic polymers provided in Examples 1-9, and the yellowness index and haze are low, and the light transmittance is high; the preparation method provided by the present invention mixes the carboxyl-containing polymer with the solution containing metal ions and then removes at least a portion of the solvent by drying. This step enables the carboxyl-containing polymer and the metal compound to be uniformly mixed, so that the two are fully reacted in the reaction zone of the twin-screw extruder, reducing white spots caused by unreacted, and improving its yellowness, haze and light transmittance to a certain extent.

[0149] From the comparison between Example 1 and Example 2, it can be seen that the yellowness index and haze of the ionic polymer obtained in Example 2 are relatively low, and the light transmittance is relatively high, which proves that improving the uniformity of mixing the carboxyl-containing polymer and the metal compound can improve the optical properties of the ionic polymer.

[0150] From the comparison of Example 1, Example 3, Example 4 and Comparative Example 6, it can be seen that the ionic polymers obtained in Examples 1, 3 and 4 have no white spots, indicating that the molar ratio of metal ions to carboxyl groups in the carboxyl-containing polymer is controlled within a suitable range, so that the two can be mixed evenly and react fully, while the ionic polymer obtained in Comparative Example 6 has white spots and relatively poor optical properties. This is because the molar ratio of metal ions to carboxyl groups in the carboxyl-containing polymer in Comparative Example 6 is too large, so that the neutralization degree of the obtained ionic polymer is too high, thereby deteriorating its optical properties to a certain extent.

[0151] It can be seen from Example 1 and Examples 5-9 that by selecting a carboxyl-containing polymer with a suitable melt index and a suitable metal compound, the two can be mixed evenly and reacted fully, and the prepared ionic polymer has no white spots and excellent optical properties.

[0152] From the comparison between Example 1 and Comparative Example 1, it can be seen that the ionic polymer obtained in Comparative Example 1 has white spots, and has a relatively high yellowness index and a relatively low transmittance. This is because in Comparative Example 1, the mixture of the metal ion-containing solution and the carboxyl-containing polymer is not dried, the two are not mixed evenly, and the solvent content in the mixture is high. The devolatilization procedure cannot completely remove the residual solvent, which leads to the appearance of white spots and affects the optical properties of the ionic polymer to a certain extent.

[0153] From the comparison between Example 1 and Comparative Example 2, it can be seen that Comparative Example 2 requires a liquid metering pump, while the preparation method provided in the present application does not require a liquid metering pump, the equipment is simpler, and the ionic polymer obtained in Comparative Example 2 has white spots and has a relatively high yellowness index, haze and relatively low transmittance. This is because the metal ion-containing solution and the carboxyl-containing polymer are not mixed evenly, and too much solvent is introduced by adding the metal ion-containing solution through a liquid metering pump, resulting in the inability to completely remove the residual solvent in the devolatilization procedure, resulting in the appearance of white spots and affecting the optical properties of the ionic polymer to a certain extent.

[0154] From the comparison between Example 1 and Comparative Example 3, it can be seen that the ionic polymer obtained in Comparative Example 3 has white spots and has a relatively high yellowness index, haze and relatively low transmittance. This is because the metal compound powder is directly mixed with the carboxyl-containing polymer, which makes the mixing of the two not uniform and the reaction not sufficient, so that the metal compound residue causes the white spot phenomenon and deteriorates the optical properties of the obtained ionic polymer to a certain extent.

[0155] From the comparison between Example 1 and Comparative Example 4, it can be seen that the ionic polymer obtained in Comparative Example 4 has white spots and has a relatively high yellowness index and a relatively low transmittance. This is because the metal compound is added through the feed port of the twin-screw extruder and then melted and reacted with the carboxyl-containing polymer, which makes the two mixed not uniformly and the reaction is not sufficient, resulting in the generation of white spots and affecting the optical properties of the obtained ionic polymer to a certain extent.

[0156] From the comparison between Example 1 and Comparative Example 5, it can be seen that the ionic polymer obtained in Comparative Example 5 has white spots and has a relatively high yellowness index and a relatively low transmittance. This is because the solvent content in the mixture formed by the carboxyl-containing polymer and the metal ion-containing solution in Comparative Example 5 is too high, and it is difficult to fully remove the solvent through the subsequent devolatilization procedure. At the same time, due to the high solvent content, the metal compound cannot be converted into a solid state, and the carboxyl-containing polymer and the metal compound are not mixed evenly, resulting in the obtained ionic polymer having white spots.

[0157] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an ionic polymer, It is characterized in that The preparation method comprises: mixing a carboxyl group-containing polymer with a solution containing metal ions to obtain a first mixture; Removing the solvent from the first mixture to obtain a second mixture; based on the mass of the solvent being 100%, the mass of the removed solvent is 50-100%; The second mixture is reacted to obtain the ionic polymer.

2. The preparation method according to claim 1, It is characterized in that The concentration of carboxyl groups in the carboxyl group-containing polymer is 0.2-25 mol %, more preferably 1-12 mol %; Preferably, the melt index of the carboxyl-containing polymer at 2.16 kg and 190° C. is 1-1000 g / 10 min, more preferably 20-600 g / 10 min; Preferably, the carboxyl-containing polymer comprises a copolymer of an α-olefin and an unsaturated carboxylic acid monomer and / or an unsaturated carboxylic acid derivative monomer; Preferably, the α-olefin has 2-8 carbon atoms, more preferably 2-3; Preferably, the unsaturated carboxylic acid monomer includes any one or a combination of at least two of acrylic acid, methacrylic acid, ethacrylic acid, itaconic acid, maleic acid or fumaric acid; Preferably, the unsaturated carboxylic acid derivative monomer includes any one of methyl hydrogen maleate, ethyl hydrogen maleate, propyl hydrogen maleate, hexyl hydrogen maleate, ethyl hydrogen fumarate or maleic anhydride, or a combination of at least two thereof; Preferably, the carboxyl group-containing polymer includes any one of ethylene-methacrylic acid copolymer, ethylene-acrylic acid copolymer or ethylene-ethylacrylic acid copolymer, or a combination of at least two thereof.

3. The preparation method according to claim 1 or 2, It is characterized in that The metal ions include metal ions formed by at least one metal in Group IA, Group IIA, Group IIIA or transition metals of the periodic table; Preferably, the chemical valence of the metal ion includes any one of monovalent, divalent or trivalent, or a combination of at least two; Preferably, the metal ions include any one or a combination of at least two of lithium ions, sodium ions, potassium ions, rubidium ions, cesium ions, beryllium ions, magnesium ions, calcium ions, strontium ions, barium ions or zinc ions, more preferably any one or a combination of at least two of potassium ions, sodium ions, lithium ions, magnesium ions, calcium ions or zinc ions, more preferably any one or a combination of at least two of potassium ions, sodium ions, lithium ions or zinc ions.

4. The preparation method according to any one of claims 1 to 3, It is characterized in that The metal ions are derived from metal compounds, and the metal compounds include any one of metal hydroxides, metal inorganic salts or metal organic salts, or a combination of at least two thereof; Preferably, the metal hydroxide includes any one of lithium hydroxide, sodium hydroxide or potassium hydroxide, or a combination of at least two thereof; Preferably, the metal inorganic salt comprises zinc sulfate and / or zinc chloride; Preferably, the metal organic salt comprises any one or a combination of at least two of sodium acetate, calcium acetate, magnesium acetate, zinc acetate or zinc formate; Preferably, the metal compound comprises any one or a combination of at least two of lithium hydroxide, sodium hydroxide, potassium hydroxide or zinc acetate; Preferably, the solution containing metal ions is obtained by mixing the metal compound with the solvent; Preferably, the solvent includes any one of water, methanol or ethanol or a combination of at least two thereof, more preferably water; Preferably, based on 100% of the mass of the solution containing metal ions, the mass of the metal compound is 30-50%.

5. The preparation method according to any one of claims 1 to 4, It is characterized in that The molar ratio of the metal ion to the carboxyl group in the carboxyl group-containing polymer is (0.2-0.7):1; Preferably, the carboxyl-containing polymer is ground into powder before the mixing; Preferably, the first mixture is dried to remove the solvent; Preferably, the drying temperature is 20-90°C, more preferably 30-70°C; Preferably, the drying time is 24-120 hours, more preferably 48-72 hours; Preferably, the drying is carried out under vacuum conditions; Preferably, based on the mass of the solvent being 100%, the mass of the solvent removed is 70-100%.

6. The preparation method according to any one of claims 1 to 5, It is characterized in that The reaction temperature is 120-300°C; Preferably, the reaction time is 5-15s; Preferably, the reaction further comprises a melting step before the reaction is carried out; Preferably, the melting temperature is 120-300°C; Preferably, the melting time is 5-15s; Preferably, after the reaction is completed, the step of devolatilizing components is further included; Preferably, the devolatilization is carried out under a vacuum degree of -10 to -950 mbar, more preferably -50 to -600 mbar; Preferably, the devolatilization time is 30-60 seconds.

7. The preparation method according to claim 6, It is characterized in that The melting, reaction and devolatilization are carried out in a continuous extrusion system; Preferably, the continuous extrusion system comprises a twin-screw extruder and / or a single-screw extruder; Preferably, the twin-screw extruder comprises a co-rotating meshing twin-screw extruder or a counter-rotating meshing twin-screw extruder; Preferably, the screw aspect ratio of the continuous extrusion system is (30-56):1; Preferably, after the devolatilization is completed, the process further comprises the steps of sequentially cooling and granulating the reaction product.

8. The preparation method according to any one of claims 1 to 7, It is characterized in that The preparation method specifically comprises the following steps: (1) mixing a metal compound with water to obtain a solution containing metal ions; and mixing a carboxyl group-containing polymer with the solution containing metal ions to obtain a first mixture; The carboxyl concentration of the carboxyl polymer is 0.2-25 mol %; the melt index of the carboxyl polymer under the conditions of 2.16 kg and 190° C. is 1-1000 g / 10 min; The mass of the metal compound is 30-50% based on the mass of the solution containing metal ions being 100%; The molar ratio of the metal ion to the carboxyl group in the carboxyl group-containing polymer is (0.2-0.7):1; (2) drying the first mixture under vacuum conditions at 20-90° C. for 24-120 h to remove 50-100 wt % of water in the first mixture to obtain a second mixture; (3) adding the second mixture to a continuous extrusion system, the continuous extrusion system comprising a melting zone, a reaction zone and a devolatilization zone; the second mixture is melted in the melting zone at a temperature of 120-300°C for a time of 5-15 seconds; the melted material reacts in the reaction zone at a temperature of 120-300°C for a time of 5-15 seconds; the reaction product is devolatilized in the devolatilization zone at a vacuum degree of -10 to -950 mbar for 30-60 seconds; the devolatilization reaction product is extruded, cooled and granulated in sequence to obtain the ionic polymer.

9. An ionic polymer, It is characterized in that The ionic polymer is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the ionic polymer according to claim 9 in sports equipment, cosmetic containers, perfume containers, food packaging, glass composite layers, automotive parts, medical vacuum skin packaging or polar exploration equipment.

Citation Information

Patent Citations

  • Ionic cross-linking process for ethylene copolymers

    EP0193110A2

  • Ionic hydrocarbon polymers

    US3264272A

  • Ionomer-modified polyethylene as film material

    US4882393A